Media and Women’s Economy: an Empirical Analysis of Gender Equality Construction of Salafi Congregation in Lampung - Nugroho, Dwi; Setyawan, Dharma; Mansyur, Abdurrahman; Yunita, Dewi Sri (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
Gender equality is an important aspect of building harmony in the family. Salafis, with their teachings of Islamic purity, is considered a religious organization that severely restricts women's activities. This reality makes the public think that Salafi women are domesticated, subordinated, and discriminated against in terms of gender. This study examines and explores the concept of gender equality in the Salafi family and how it is contextualized in reality and women's economic movements. This qualitative research uses observational data, periodic WhatsApp application interviews, and documentation studies. This study shows that, first, an understanding of gender equality has been developed in Salafi families in Lampung, although its implementation still requires negotiation by considering the rights and obligations of women in the family, as wives, mothers, and both. Second, while still paying attention to religious norms, Salafi women utilize social media, the internet, and digital technology to build businesses, partner, and connect with many parties. Third, the creativity of Salafi women in building homes as a place for entrepreneurship, no longer a domestic space, has been able to form alliances instead of causing conflict between home and workplace and clouding public perceptions that they are domesticated.